Data Network in Development of 3D Collaborative Virtual Environments: A Systematic Review - Colombo Dias, Diego Roberto; Durelli, Rafael Serapilha; Ferreira Brega, Jose Remo [UNESP]; Gnecco, Bruno Barberi; Trevelin, Luis Carlos; Guimaraes, Marcelo de Paiva; Murgante, B.; Misra, S.; Rocha, AMAC; Torre, C.; Rocha, J. G.; Falcao, M. I.; et al. (Springer, 2014)
Background: 3D Collaborative Virtual Environments (3DCVE) have been used to allow multiple geographically distant users to share virtual reality environment. This remote user collaboration requires to deal with network problems. Objective: The objective of this systematic review is twofold: (1) to identify possible solutions to network issues, especially those related to the Internet, such as jitter, latency and packet loss; and (2) to identify the protocols and network topologies commonly used in 3DCVE. Results: We selected 132 papers from the most commonly used search portals, i.e., IEEE, ACM, Scopus, Springer, Science Direct and Web of Science. We also describe the studies conducted over the past 10 years, highlighting the network protocols and topologies, which are commonly used. Finally, we suggest a framework architecture for 3DCVE based on graphic cluster.